O curso de Tecnologia em Gestão de Cooperativas (TGC) e sua proposta formativa de gestores de cooperativas autogestionárias do MST - Almeida, Antônio Escobar de (2017)
This research presents and discusses the Educational Project of the Course of Technology in Cooperative Management (TGC) as a formative proposal of managers of self-managed cooperatives of the Landless Rural Workers Movement (MST). The main objective of the research is to analyze the training proposal of the Course for people who are out of school who will act as managers of selfmanaged cooperatives of the MST, as a proposal of formation in the perspective of construction of references for overcoming the modelo f development proper to the capitalismo Sistem and, as specific objectives. Development of the capitalist system and, as specific objectives, (a) to critically analyze the educational project of the course, its curricular and organizational components, in relation to the quality of the training practice, (b) systematize the experience of the Cooperative Management Technology course , (C) to recognize the relationship between the human training concept of the MST and the perspective of self-management from the University of Mondragon, Spain, as a technological training proposal for the partnership with the MST. For that, it is based on a contextualization of the course, finding as main reference the historical experiences of its two main subjects, the MST and the Cooperative Experience of Mondragon (ECM), who conceived the process, object of our research, as an important activity of the partnership Carried out from the year 2006, in the Central Region of the State of Paraná, region of Cantuquiriçuçú. With the collection of data along with the course documents, their Political Educational Project, the curricular and organizational components, evaluation reports, work orientation guides and course completion papers were analyzed. From the analysis of these documents, the research also sought to understand the conception and method of cooperation, education and human formation, expressed by the organizations promoting the course, which requiered understanding the necessary relationship between education, work, collective organization or self-culture, political or social Project and social transformation. The research hopes to understand how the formative proposal of the TGC Course materialized and what the possible implications that its process had for the training of managers of social enterprises and organizations where they work.